Atomic-scale modeling of superalloys - Hammerschmidt, Thomas; Rogal, Jutta; Bitzek, Erik; Drautz, Ralf (Elsevier, 2021)
Atomistic theory holds the promise for the ab initio development of superalloys based on the fundamental principles of quantum mechanics. The last years showed a rapid progress in the field. Results from atomistic modeling enter larger-scale simulations of alloy performance and often may be compared directly to experimental characterization.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Atomistic simulations; Defect formation; Defect mobility; Defect-defect interaction; Structural stability